2006
DOI: 10.1289/ehp.8786
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes Related to Endocrine Function and Decline in Reproduction in Fathead Minnow ( Pimephales promelas ) after Dietary Methylmercury Exposure

Abstract: BackgroundMethylmercury (MeHg) is a known neurotoxic agent, but the mechanisms by which MeHg may act on reproductive pathways are relatively unknown. Several studies have indicated potential changes in hormone levels as well as declines in vertebrates with increasing dietary MeHg exposure.ObjectivesThe purpose of this study was to identify alterations in gene expression associated with MeHg exposure, specifically those associated with previously observed changes in reproduction and reproductive biomarkers. Fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 46 publications
8
33
0
Order By: Relevance
“…In previous studies, exposure to environmentally related concentrations of MeHg suppressed gonadal development and estrogen production in female FHM and testosterone in male FHM (Drevnick and Sandheinrich, 2003). Therefore, MeHg may function as an endocrine disruptor by binding to estrogen receptors and acting virtually as an estrogen mimic (Klaper et al, 2006). In addition, MeHg appears to affect bone cells, inducing hypercalcemia in goldfish and interferes with calcium homeostasis (Suzuki et al, 2004).…”
Section: Mercurymentioning
confidence: 93%
“…In previous studies, exposure to environmentally related concentrations of MeHg suppressed gonadal development and estrogen production in female FHM and testosterone in male FHM (Drevnick and Sandheinrich, 2003). Therefore, MeHg may function as an endocrine disruptor by binding to estrogen receptors and acting virtually as an estrogen mimic (Klaper et al, 2006). In addition, MeHg appears to affect bone cells, inducing hypercalcemia in goldfish and interferes with calcium homeostasis (Suzuki et al, 2004).…”
Section: Mercurymentioning
confidence: 93%
“…In a controlled feeding study, Webber and Haines (2003) reported that golden shiners (Notemigonuscryso leucas), with whole-body Hg concentrations averaging 0.52 μg/g ww, were hyperactive and had altered shoaling behavior relative to fish with lower Hg concentrations. Other negative effects of Hg exposure reported in fish include impacts on reproductive parameters, such as impaired spawning behavior, mediated through a disruption of normal neuroendocrine function (Hammerschmidt et al, 2002;Drevnick and Sandheinrich, 2003;Klaper et al, 2006;Sandheinrich and Miller, 2006;Crump and Trudeau, 2009). In a critical review of the recent literature, Sandheinrich and Wiener (2010) concluded that changes in biochemical processes, damage to cells and tissues, and reduced reproduction in fish occur at MeHg concentrations of about 0.5 to 1.2 μg Hg/g ww in axial muscle.…”
Section: Comparison Of Fish Effect Levels With Mercury Concentrationsmentioning
confidence: 99%
“…Due to the speed with which physiological status can change when perturbed by abiotic stress, multiple studies have focused on the sex-specific physiological responses of fish to environmental contaminants (Aaltonen et al, 2000;Afonso et al, 2003;Klaper et al, 2006). Exposure to methylmercury (MeHg) has been shown to elicit sex-related responses in fish (Klaper et al, 2006).…”
Section: Physiologymentioning
confidence: 99%
“…Exposure to methylmercury (MeHg) has been shown to elicit sex-related responses in fish (Klaper et al, 2006). Male fathead minnows (Pimephales promelas) respond by an up-regulation of vittelogenin mRNA, while females show the opposite (i.e., down-regulation).…”
Section: Physiologymentioning
confidence: 99%